Improving Corporate Governance and Managerial Skills in Banking Organizations - Capriglione, Francesco; Casalino, Nunzio (International Journal of Advanced Corporate Learning (iJAC), 2014)
At the present, the focus on management and corporate governance of banks will play an ever more crucial role given the prevailing importance of banking institutions as a source of finance for the corporate sector. Improved board structures, administrative procedures and disclosure requirements could result in better-governed banks, which are more likely to allocate investments proficiently. Therefore, a strong corporate governance can be an important pillar for banking organizations assets, because effective boards of directors complement the regulatory oversight. Efforts to promote good corporate governance in financial institutions face a number of challenges. One is getting the most innovative and experienced people to serve on bank’s boards and management, given the complexity of the business environment and new financial products. This requires also finding competent leaders who also understand new business opportunities and their risks, have a healthy scepticism and take decisions quickly. Regulatory and supervisory frameworks alone cannot guarantee financial stability. Effective corporate governance, change management approaches and innovative managerial skills can act as a first line of defence for banks and financial institutions, against any impending crisis and unethical business practices.